Building Local Products "Bubbor Paddas" Instant Packaging Typical of Sambas into a Globally Competitive Product - Maryam, Andi; Rozana, Rozana; Tritisari, Angga; Andiyono, Andiyono; Junardi, Junardi (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to develop Bubbor Paddas, a Sambas culinary specialty, into an instant competitive product in national and international markets. The development process employed the Project-Based Learning (PBL) method, involving students and industry partners in all stages of production, including vegetable drying, seasoning preparation, packaging, and marketing. Food technology innovations, particularly in drying and packaging techniques, were applied to maintain the original flavor and texture of Bubbor Paddas. The results indicated a 30% increase in production efficiency and enhanced product packaging quality, making it more durable and visually appealing. Additionally, digital marketing strategies were implemented, leading to a 40% increase in product orders within three months of launch. This initiative not only improved the quality and competitiveness of local products but also positively impacted community empowerment and the preservation of Sambas culinary heritage. The findings highlight the importance of integrating modern technology and marketing strategies in developing innovative and sustainable traditional culinary products.